PENGEMBANGAN MULTIMEDIA INTERAKTIF MATA PELAJARAN IPA KELAS IVC SD NEGERI 034 TARAIBANGUN KABUPATEN KAMPAR - Mizana Qistina; Mahmud Alpusari; Eddy Noviana; Neni Hermita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This study aimed to develop interactive multimedia learning media for science subjects using Adobe Flash for Grade IV-C elementary school students. The development resulted in an interactive multimedia learning product packaged in the form of an interactive CD. This study employed a Research and Development (R&D) method using the 4D development model, which consists of four stages: define, design, develop, and disseminate. The results of the validation tests indicated that the interactive multimedia learning media for science subjects was categorized as valid and feasible. Validation by media experts obtained a score of 3.75, categorized as very valid, while validation by material experts resulted in a score of 3.50, also categorized as very valid. User validation yielded a score of 3.54, categorized as good. Furthermore, the effectiveness test based on the N-Gain analysis produced a value of 0.60, which falls into the medium category, indicating that the interactive multimedia learning media was effective. Based on these findings, it can be concluded that the interactive multimedia learning media for science subjects developed using Adobe Flash is feasible and effective for use in the teaching and learning process for Grade IV-C elementary school students.